Effect of Sagittal Dentoskeletal Discrepancies on the Vermilion Height and Lip Area - Arun Joseph; Shobha Sundareswaran; Sandhya Srinivas (Galenos Yayinevi, 2019)
Objective:A frontal evaluation of the lips could provide important information during a routine clinical evaluation of facial aesthetics. There is a lack of ample evidence in the literature regarding variations in the vermilion height and lip area in various sagittal discrepancies when assessing facial aesthetics. The aim of this cross-sectional study was to evaluate and compare the vermilion height and lip area in dentoskeletal Class I, Class II, and Class III malocclusions.Methods:Subjects included female patients divided into four groups (Angle's Class I bimaxillary proclination [Class I BMP], Class II Division I [Class II Div 1], Class III and Class I normal [Class I N]) with 36 samples each. Standardized frontal facial photographs were taken at rest and during a posed smile. Thirty-five landmarks on the upper and lower lips were identified for measurements of the vermilion height and lip area. A one-way analysis of variance was used to identify overall differences, and the post-hoc Bonferroni test was applied for multiple comparisons.Results:Class III showed a significantly smaller upper-lip area and significantly higher ratios of the upper-to-lower lip vermilion height/area. The ratios displayed an increasing trend from the midline to the corners of the mouth. Class I BMP and Class II Div 1 had significantly larger upper and lower-lip areas.Conclusion:Morphology of the lips is significantly correlated with underlying anteroposterior dentoskeletal discrepancies. During a clinical examination, a critical frontal evaluation of the lips is important as it is apparently indicative of the underlying sagittal discrepancy, especially in skeletal Class III malocclusions.